Differentiated Learning in Islamic Religious Education: Solutions for the Diversity of Student Learning Styles - Ramadani, Fazrineka; Nurul Latifatul Inayati (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research describes using differentiated learning from PAI materials in SMA Negeri 1 Tawangsari. Then, this research also explores the factors supporting and inhibiting differentiated learning. The design used is a qualitative descriptive design. The data collected using interview design and observation will be analyzed using qualitative data analysis. The research results show that differentiated learning in PAI materials at SMA Negeri 1 Tawangsari includes three main types: content differentiation, process differentiation, and product differentiation, tailored to the three primary learning styles: auditory, visual, and kinesthetic. Supporting factors for differentiated learning involve aligning learning types with students' interests, talents, and learning styles despite individual differences. On the other hand, inhibiting factors include students' misuse of mobile phones. The evaluation of differentiated learning positively impacts student achievement, which ultimately shapes their interests, talents, and learning styles, leading to more optimal learning outcomes.